Business Performance Based on Entrepreneurial Orientation, Motivation, and Organizational Commitment in Snack Food MSMEs - Silaningsih, Endang; Kartini, Tini; Ibrahim, Zahra Azkia (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2024)
This study examines the effect of entrepreneurial orientation and motivation on business performance with organizational commitment as an intervening variable in snack food MSMEs in Cisarua District. The sample used was 58 snack food MSMEs in Cisarua District. This research is descriptive and verification with the path analysis method. This study resulted in the findings that entrepreneurial orientation and motivation have an influence on business performance and organizational commitment. Organizational commitment served as an intervening variable. Based on the result of this study, business actors must be able to improve entrepreneurial orientation and motivation in order to improve business performance and organizational commitment.